GENDER-BASED COMMUNICATIVE STRATEGIES IN CHILD DISCOURSE: A PRAGMATIC AND CROSS-CULTURAL PERSPECTIVE (World Bulletin of Social Sciences, 2025)
This article explores the communicative strategies used by children to express and perform gender in both Uzbek and English linguistic and cultural contexts. Building on the theoretical framework of Shokirova Dilorom’s dissertation, the study investigates how boys and girls employ language differently in interaction, and how these differences are shaped by socio-cultural norms, discourse models, and pragmatic competence. The research applies a comparative approach, integrating data from authentic child dialogues, literary texts, and children’s folklore. The study reveals that boys and girls tend to adopt distinctive communicative strategies, such as different uses of directives, mitigation, politeness markers, and humor, which reflect culturally sanctioned gender roles. While Uzbek children's speech is characterized by more hierarchical, role-based discourse strategies, English-speaking children display relatively egalitarian and expressive speech behavior. The analysis employs pragmatic tools such as Grice’s maxims, speech act theory, and conversational analysis to examine how gender emerges not only as a biological or psychological category, but also as a discursive construct shaped through strategic language use. The study concludes that gendered communication in children is a dynamic process that both mirrors and perpetuates cultural ideologies. These findings contribute to the fields of gender linguistics, child pragmatics, and intercultural communication.